How Are Cytochrome b561 Electron Currents Controlled by Membrane Voltage and Substrate Availability? - Picco, C.; Scholz-Starke, J.; Naso, A.; Preger, V.; Sparla, F.; Trost, P.; Carpaneto, A. (Antioxidants & Redox Signaling, 2014)
Abstract Direct recordings of electron currents mediated by cytochromes b561 (CYB561) are not available yet, despite the importance of these proteins in a variety of physiological functions, including neurotransmitter synthesis and dietary iron uptake. Here, we used the two-electrode voltage-clamp technique applied to Xenopus oocytes to demonstrate, for the first time, the generation of electron currents by a Drosophila member of the CYB561 superfamily named stromal cell-derived receptor 2 (SDR2). This experimental method, along with the theoretical development of a three-state kinetic model, supports the hypothesis that electron donor/acceptor concentrations and transmembrane voltage mutually control SDR2-mediated electron transport activity in a complex but predictable manner. Antioxid. Redox Signal. 21, 384-391.